Sense and sensibility – Online forums as epistemic arenas. (September 2016) - Landqvist, Mats
Abstract: From a discourse analytic framework, this article analyses an online forum in which users give each other support in relation to a medical problem. The article relates sequences of dialogue between active users in this health forum from the perspective of digital literacy, informational support giving and rapport building. Taking into account previous studies on communication via medical forums, support giving and identity construction, this study develops and proposes some key strategies of explication of how knowledge plays a key role and is assigned to establishing contact as well as adapting themselves to other users of the forum. The role of epistemic parts in the forums is displayed through (1) encouraging further interaction, (2) bonding, and (3) attracting eligible dialogue partners. Skilful users are shown to share knowledge with each other in an informal, yet specific and substantial way. Posters are authored in flexible ways through a balance between knowledge input and emotional support giving. Knowledge is thus framed by the effects of the entanglement of epistemic and affective stances – not only by information exchanges. Highlights: This paper adopts online data to examine stances in a forum for health problems. Literacy and dialogicity combined form a useful analytical framework. The role of epistemic parts in the forums is displayed through the following: (1) encouraging further interaction, (2) bonding, (3) attracting eligible dialogue partners. Knowledge is assigned to establishing contact and adapting to other users.